Peran Digitalisasi Dalam Meningkatkan Efektivitas Pembayaran Pajak Kendaraan Bermotor : (Studi Kasus Kota Binjai) - Nurliza Pratiwi; Junawan Junawan (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study aims to determine the role of digitalization in increasing the effectiveness of motor vehicle tax payments in Binjai City. This study uses a descriptive qualitative approach with data collection including observation, interviews, and documentation. The informants in this study consisted of 1 key informant and 3 supporting informants. The results of this study show that there are still many taxpayers who have difficulties in understanding the registration flow, payment methods, and printing documents such as SKPD. The lack of clear guidance in the application as well as delays in the submission of physical documents are the main obstacles. Therefore, the tax office in Binjai City has made various efforts to increase the effectiveness of Motor Vehicle Tax (PKB) payments. One way is to develop digital services that allow taxpayers to pay taxes online, so that it is faster and more efficient. In addition, officers also provide information media such as banners, video tutorials, and conduct direct counseling to the village office to increase public understanding of the digital payment mechanism.